Lifetime Cost of Abusive Head Trauma at Ages 0–4, USA - Miller, Ted; Steinbeigle, R.; Lawrence, B.; Peterson, C.; Florence, C.; Barr, M.; Barr, R. (Routledge, 2017)
This paper aims to estimate lifetime costs resulting from abusive head trauma (AHT) in the USA and the break-even effectiveness for prevention. A mathematical model incorporated data from Vital Statistics, the Healthcare Cost and Utilization Project Kids’ Inpatient Database, and previous studies. Unit costs were derived from published sources. From society’s perspective, discounted lifetime cost of an AHT averages $5.7 million (95% CI $3.2–9.2 million) for a death. It averages $2.6 million (95% CI $1.0–2.9 million) for a surviving AHT victim including $224,500 for medical care and related direct costs (2010 USD). The estimated 4824 incident AHT cases in 2010 had an estimated lifetime cost of $13.5 billion (95% CI $5.5–16.2 billion) including $257 million for medical care, $552 million for special education, $322 million for child protective services/criminal justice, $2.0 billion for lost work, and $10.3 billion for lost quality of life. Government sources paid an estimated $1.3 billion. Out-of-pocket benefits of existing prevention programming would exceed its costs if it prevents 2% of cases. When a child survives AHT, providers and caregivers can anticipate a lifetime of potentially costly and life-threatening care needs. Better effectiveness estimates are needed for both broad prevention messaging and intensive prevention targeting high-risk caregivers.